Supervised training in primary care units but not self-directed physical activity lowered cardiovascular risk in Brazilian low-income patients: a controlled trial - Amana M. Lima; André O. Werneck; Edilson Cyrino; Paulo Farinatti (BMC, 2019)
Abstract Background Public health strategies to increase physical activity in low-income communities may reduce cardiovascular risk in these populations. This controlled trial compared the cardiovascular risk estimated by the Framingham Risk Score (FRS) over 12 months in formally active (FA), declared active (DA), and physically inactive (PI) patients attended by the 'Family Health Strategy' in low-income communities at Rio de Janeiro City, Brazil (known as 'favelas'). Methods Patients were matched for age and assigned into three groups: a) FA (supervised training, n = 53; 60.5 ± 7.7 yrs); b) DA (self-reported, n = 43; 57.0 ± 11.2 yrs); c) PI (n = 48; 57.0 ± 10.7 yrs). FA performed twice a week a 50-min exercise circuit including strength and aerobic exercises, complemented with 30-min brisk walking on the third day, whereas DA declared to perform self-directed physical activity twice a week. Comparisons were adjusted by sex, chronological age, body mass index, and use of anti-hypertensive/statin medications. Results At baseline, groups were similar in regards to body mass, body mass index, triglycerides, and LDL-C, as well to FRS and most of its components (age, blood pressure, hypertension prevalence, smoking, HDL-C, and total cholesterol; P > 0.05). However, diabetes prevalence was 10-15% lower in DA vs. FA and PI (P < 0.05). Intention-to-treat analysis showed significant reductions after intervention (P < 0.05) in FA for total cholesterol (~ 10%), LDL-C (~ 15%), triglycerides (~ 10%), systolic blood pressure (~ 8%), and diastolic blood pressure (~ 9%). In DA, only LDL-C decreased (~ 10%, P < 0.05). Significant increases were found in PI (P < 0.05) for total cholesterol (~ 15%), LDL-C (~ 12%), triglycerides (~ 15%), and systolic blood pressure (~ 5%). FRS lowered 35% in FA (intention-to-treat, P < 0.05), remained stable in DA (P > 0.05), and increased by 20% in PI (P < 0.05). Conclusions A supervised multi-modal exercise training developed at primary care health units reduced the cardiovascular risk in adults living in very low-income communities. The risk remained stable in patients practicing self-directed physical activity and increased among individuals who remained physically inactive. These promising results should be considered within public health strategies to prevent cardiovascular disease in communities with limited resources. Trial registration TCTR20181221002 (retrospectively registered). Registered December 21, 2018.